SuperDARN E-region backscatter boundary in the dusk-midnight sector – tracer of equatorward boundary of the auroral oval - P. T. Jayachandran; P. T. Jayachandran; E. F. Donovan; J. W. MacDougall; D. R. Moorcroft; J.-P. St. Maurice; P. Prikryl (Annales Geophysicae, 2002)
We compare the locations of the equatorward boundaries of SuperDARN E-region backscatter and Hb  emissions, focusing on the dusk-midnight sector of the auroral oval where the proton aurora is statistically located equatorward of the discrete electron aurora. We show that, whenever both boundaries can be simultaneously identified, they are coincident. Our result complements earlier studies, which demonstrated the correspondence between the DMSP b2i boundary and both the equatorward boundary of the proton auroral oval (Donovan et al., 2002), and the equatorward boundary of SuperDARN E-region echoes (Jayachandran et al., 2002). Further, our result shows that, provided there is sufficient precipitating proton energy flux, the SuperDARN radars can be used to monitor the equatorward edge of the proton auroral oval. Key words. Ionosphere (auroral ionosphere; particle precipitation; ionospheric irregularities)